Using Habitat Characteristics to Predict Faunal Diversity in Tropical Production Forests. (30th September 2013) - Lam, Tzeng Yih; Fletcher, Christine; Ramage, Benjamin S.; Doll, Hannah M.; Joann, C. Luruthusamy; Nur‐Zati, A. Mustafa; Butod, Elizabeth; Kassim, Abdul R.; Harrison, Rhett D.; Potts, Matthew D.
Abstract Biodiversity conservation in managed tropical forests is becoming increasingly important as forest area continues to decline. Accordingly, there is growing interest in developing conservation‐driven silvicultural prescriptions and identifying indicator habitat metrics (similar to indicator taxa) that could be easily assessed via routine vegetation sampling. Successfully achieving these goals, however, requires an understanding of how habitat characteristics affect biodiversity. The purpose of this study was to determine the associations between the species diversity of three taxa (ants, insectivorous bats, and dung beetles) and the habitat characteristics of hill dipterocarp production forests. We sampled both within (three samples) and adjacent to (six samples) six Virgin Jungle Reserves distributed throughout Peninsular Malaysia, and related habitat predictors to univariate diversity metrics (species richness and Shannon diversity) as well as multivariate compositional metrics. We found that influential predictors and directional effects differed across taxa. Ant diversity was most affected by stand density and canopy cover, and positively associated with both. Bat diversity was most strongly linked to primary forest area, with smaller reserves harboring greater bat diversity. Dung beetles were most affected by canopy cover and elevation, with greater diversity at lower elevation and with less canopy cover. Our multivariate analyses did not reveal any strong relationships between species composition and habitat variables. Overall, our results provide evidence that tropical forest structure is associated with biodiversity, but also suggest that it will be difficult to identify a single silvicultural prescription or landscape management strategy to maximize the diversity of all three taxa simultaneously.